A preferência da geração de millennials pela locação de imóveis e suas consequências no mercado imobiliário brasileiro - Ferreira, Amanda Pina (2020)
The generation of millennials represents 33% of the Brazilian population and due to their purchasing power, millennials are changing the way they consume products in the real estate market, not only in Brazil, but in the rest of the world. From the point of view of demand, the growth in real estate prices in Brazil (from 2004 to 2013) and in the world (from 1997 to 2015) above inflation and income made this generation, when entering the job market, suffer for not having enough purchasing power to finance their own home. Consequently, the propensity of families for leasing has also been growing throughout Brazil since 2000, more intensively in the city of São Paulo. This work analyzes the theme from the point of view of demand, understanding what happened to the rental market for residential properties in Brazil and in the world, as well as doing a survey through a questionnaire with millennials living in the city of São Paulo to understand the preference of themselves by purchasing or renting a property. From the supply point of view, the study sought to understand whether there is financial viability for the construction and operation of a residential development focused 100% on leasing. The residential segment for rent is already consolidated in several countries around the world and given the low interest scenario in Brazil, with income developments proving to be more efficient in services and with a safer legal structure for property owners, it is important reflect and analyze on this topic. It was concluded from the questionnaire applied that millennials from São Paulo are more likely to rent than to buy the property. The case study, on the other hand, proved that there is financial and economic viability for a residential development for income with returns above the minimum rate of attractiveness in the market